2015
DOI: 10.1002/2014jd023022
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Arctic mixed‐phase cloud structure and its relationship with humidity and temperature inversion using ARM NSA observations

Abstract: In this study, the characteristics of the Arctic mixed-phase cloud (AMC) have been investigated using data collected at the Atmospheric Radiation Measurement North Slope Alaska site from October 2006 to September 2009. AMC has an annual occurrence frequency of 42.3%, which includes 18.7% of single-layered AMCs and 23.6% for multiple layers. Two cloud base heights (CBHs) are defined from ceilometer and micropulse lidar (MPL) measurements. For single-layered AMC, the ceilometer-derived CBH represents the base of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 37 publications
2
30
1
Order By: Relevance
“…This result is similar to results found by Kim et al (2008) differ by about 0.20. In a stable atmosphere with high LTS it appears that ACI net LWP increases more strongly in response to aerosols than in unstable environments (Klein and Hartmann, 1993;Qiu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to results found by Kim et al (2008) differ by about 0.20. In a stable atmosphere with high LTS it appears that ACI net LWP increases more strongly in response to aerosols than in unstable environments (Klein and Hartmann, 1993;Qiu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…On a regional scale, low-level MPCs were studied extensively in the Arctic, where they occur frequently and are persistent [67,78,89,103]. MPCs may be stabilized due to anthropogenic activity due to the deactivation effect [25] such that the sulfate-induced inhibition of freezing leads to fewer and larger ice crystals both in MPCs and pure ice clouds [27].…”
Section: Aerosol Effects On Stratiform and Shallow Convective Mpcsmentioning
confidence: 99%
“…It is because results shown here are the median values and relative frequency distributions for all sounding profiles; if inversions exhibited at different levels relative to the cloud, they will be averaged out. Statistics of the inversions on a profile‐by‐profile basis would show a different result, as was done in Qiu et al (). The specific humidity inversions below the cloud base could be due to the deposition of water vapor on the falling ice crystals in the sub‐cloud layer, which would cause the specific humidity to decrease.…”
Section: Resultsmentioning
confidence: 95%
“…That is, the strong backscatter data from the ceilometer and MPL, combined with the small depolarization ratio from the MPL, indicate the existence of liquid phase droplets in this layer. Qiu et al () found that the MPL‐defined Z b is usually several hundred meters to 1 km lower than the ceilometer Z b . In the region between Z b,MPL and Z b,ceil , the backscatter data range from 8 to 30 × 10 −6 /m·sr, the depolarization data fall between a range of 0.1–0.5, and the Doppler velocity is often less than 1 m/s (Qiu et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation